Desiminasi Uji Unjuk Kerja Alat Penyuling Air Mawar (Rose Water) Kepada Mahasiswa MBKM dan Teknisi Laboratorium - Budi Hariono; Mokhammad Fatoni Kurnianto; Abi Bakri; Findi Citra Kusumasari (Indonesian Journal Publisher, 2025)
The main obstacle for rose farmers is the inability to maintain the freshness of the flowers, which quickly wilt and are thrown away after 3-5 days of harvest. Because innovation is needed to process rose flower waste into products with high selling value and become essential oils. The main problem in the machine tool design process, especially distillation machine tools, is that the process efficiency of the machine tool is not yet known. This has a big influence on the yield of essential oils obtained and is inefficient in using fuel. The aim of this program is to provide knowledge and skills to participants, namely 7 MBKM student participants and technicians from laboratories (agricultural machine tools and energy laboratories). The results of calculating the efficiency of the rose water distiller are as follows: (a) the efficiency of the distilling kettle vessel is 22.91%; (b) condenser efficiency of 77.08% and (c) total distiller efficiency of 17.66%. The recommendation that needs to be made is to increase the efficiency of the distilled kettle by providing an insulator along the distilled kettle.